2016
DOI: 10.15249/10-1-107
|View full text |Cite
|
Sign up to set email alerts
|

Bank customers’ preferences and responses to Corporate Social Responsibility (CSR) initiatives in Ghana

Abstract: The study sought to investigate Ghanaian bank customers' ranked preference for corporate social responsibility (CSR) initiatives and determine which initiative has the greatest effect on their attitudes and behaviour toward banks. A sample of 384 retail bank customers was employed in the study. The study applied a one-way MANOVA and two univariate ANOVAs. The study found that customers have the highest preference for corporate philanthropy initiatives, followed by customercentric and community volunteering ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The evidence obtained suggests that philanthropic CSR issues lead to positive customer reactions towards banks. In tandem with the findings by Hinson, Renner and van Zyl (2016), Alomenu, Effah and Kutu-Adu (2015) also found that CSR practices of Ghanaian banks were mostly philanthropic and altruistic. The authors also established a positive relationship between CSR and customers' selection of and long-term relationship with banks.…”
Section: Banking Sectorsupporting
confidence: 70%
See 4 more Smart Citations
“…The evidence obtained suggests that philanthropic CSR issues lead to positive customer reactions towards banks. In tandem with the findings by Hinson, Renner and van Zyl (2016), Alomenu, Effah and Kutu-Adu (2015) also found that CSR practices of Ghanaian banks were mostly philanthropic and altruistic. The authors also established a positive relationship between CSR and customers' selection of and long-term relationship with banks.…”
Section: Banking Sectorsupporting
confidence: 70%
“…The authors also established a positive relationship between CSR and customers' selection of and long-term relationship with banks. On CSR information needs of customers of Microfinance Institutions (MFI) in Ghana, Okoe and Boateng (2016) however found that such needs were primarily ethical and economic than legal and philanthropic, contrary to the findings by Hinson et. al.…”
Section: Banking Sectormentioning
confidence: 65%
See 3 more Smart Citations